An analysis of volatility and dependence between rubber spot and futures prices using copula-extreme value theory - Phattanan Boonyanuphong (2018)
This paper aims to estimate the dependency between spot rubber price and futures prices using the copula-extreme value theory based on semi-parametric approaches, which combine copula functions with the conditional extreme value theory to construct the dependence models. The C-EVT model is used to estimate the marginal distributions of the returns of rubber spot price and futures prices that enable the model's flexibility for the tail behavior. Both static and time-varying copulas are applied to construct the dependence structure between the returns of the rubber spot price and the futures prices. The empirical results showed weak spotfutures dependence between the spot rubber price and the futures prices of Thai markets, implying that we could not accept the efficient market hypothesis. However, we found symmetric tail dependence between the spot rubber price and the futures prices of the Singapore, Tokyo, and Shanghai markets. This means that cash rubber price is do minated by the futures prices of the Singapore, Tokyo, and Shanghai markets. The best-fitting dependence models are the time-varying t-copulas, but the tail dependence for all pairs is relatively low. This result means that the futures prices are weak in explaining the changes in spot prices under extreme events. © Springer International Publishing Switzerland 2014.